Performance and Participation in the 'Vasaloppet' Cross-Country Skiing Race during a Century - Nastja Romancuk; Pantelis T. Nikolaidis; Elias Villiger; Hamdi Chtourou; Thomas Rosemann; Beat Knechtle (MDPI AG, 2019)
This study investigated gender differences in performance and participation and the role of nationality during one century in one of the largest cross-country (XC) skiing events in the world, the ‘Vasaloppet‘ in Sweden. The total number of female and male athletes who finished (n = 562,413) this race between 1922 and 2017 was considered. Most of the finishers were Swedish (81.03% of women and 88.39% of men), followed by Norwegians and Finnish. The overall men-to-women ratio was 17.5. A gender × nationality association was observed for participation (χ2 = 1,823.44, p < 0.001, φ = 0.057), with the men-to-women ratio ranging from 6.7 (USA) to 19.1 (Sweden). For both genders, the participation (%) of Swedish decreased, and that of all other nationalities (except Swiss) increased across years. Regarding the mean race time, men were faster than women by 14.5% (7 h 52 min 17 s versus 9 h 00 min 55 s, respectively). A trivial gender×nationality interaction regarding the race time was observed (p < 0.001, η2 < 0.001), with gender differences ranging from 4.4% (USA) to 22.0% (Iceland). The race time increased across calendar years for both women (r = 0.45, p = 0.006, moderate magnitude) and men (r = 0.25, p = 0.015, small magnitude). On the basis of these findings, we concluded that a relatively small number of women pariticipates in XC skiing. Therefore, the development of public health policies targeting the participation of women in XC skiing should be a concern in the countries with a tradition of this sport.